PHYTANE FROM CHEMOLYTIC ANALYSIS OF MODERN MARINE SEDIMENTS: A PRODUCT OF DESULFURIZATION OR NOT? - Prahl F.G.; Pinto L.A.; Sparrow M.A. (My University, 1996)
A set of modern marine sediments was analyzed to evaluate the role of sulfurization as a mechanism for biomarker preservation during early diagenesis. The set consisted of sediments accumulating within various oxic to anoxic depositional environments. Raney nickel treatment of the polar fraction of total extractable lipids (pTEL) from each sample yielded 3,7,11,15-tetramethylhexadecane ('phytane') as the dominant product, accompanied in several cases by minor levels of C27, C28, and C29 5α/β(H)-steranes, n-C31 alkane, and β-carotane. Although others have ascribed such products to a desulfurization reaction, our work reveals significant production of phytane from the action of Raney nickel on the esterified side chain of chlorophyll. Results suggest that catalytic dehydration/hydrogenation of chlorophyll accounts for #50 and #4% of the Raney nickel phytane (rnPhy) yield measured in suboxic sediments from the Washington shelf and anoxic sediments from Saanich Inlet, respectively. If 8-20% of the pheopigment detected in the suboxic sediments and all of the pheopigment detected in the anoxic sediment exists as pheophytin, the catalytic dehydration/hydrogenation process would account for 100 and 50%, respectively, of the observed rnPhy yield. The collective findings from our work underscore the necessity to exercise extreme caution when interpreting the geochemical significance of hydrocarbon products from Raney nickel treatment of pTEL from sediments. Despite the organic chemical fact that Raney nickel is a well-known desulfurizing agent, desulfurization cannot be assigned necessarily as the source of hydrocarbons generated by the action of this reagent on complex lipid extracts from sediments, particularly those from modern environments.